Genome‐wide profiling of normal gastric mucosa identifies Helicobacter pylori‐ and cancer‐associated DNA methylome changes. Issue 3 (6th April 2018) - Woo, Hae Dong; Fernandez‐Jimenez, Nora; Ghantous, Akram; Degli Esposti, Davide; Cuenin, Cyrille; Cahais, Vincent; Choi, Il Ju; Kim, Young‐Il; Kim, Jeongseon; Herceg, Zdenko
Abstract : The large geographic variations in the incidence of gastric cancer (GC) are likely due to differential environmental exposures, in particular to Helicobacter pylori ( H. pylori ) infection. We aimed to investigate the impact of H. pylori on the epigenome in normal gastric mucosa and methylation changes associated with cancer risk independent of H. pylori . A discovery set of normal gastric mucosa from GC cases ( n = 42) and controls ( n = 42), nested in a large case–control study and stratified by H. pylori status, were subjected to genome‐wide methylation profiling. Single‐nucleotide polymorphism arrays from peripheral blood leukocytes were used to conduct methylation quantitative trait loci (mQTL) analysis. A validation set of gastric mucosa samples ( n = 180) was used in the replication phase. We found 1, 924 differentially methylated positions (DMPs) and 438 differentially methylated regions (DMRs) associated with H. pylori infection, most of which were hypermethylated. Significant methylation alterations identified in the initial set were successfully replicated. Furthermore, the H. pylori ‐associated DMP/Rs showed marked stability ('epigenetic memory') after H. pylori clearance. Interestingly, we found 152 DMRs associated with cancer risk independent of the H. pylori status in normal gastric mucosa. The methylation score derived from three biomarkers was a strong predictor of GC. Finally, the mQTL analysis indicated that the H. pylori ‐ and cancer‐specific methylation signatures were minimally affected by genetic variation. The comprehensively characterized methylome changes associated with H. pylori infection and GC risk in our study might serve as potential biomarkers for early cancer progression in tumour‐free gastric mucosa. Abstract : What's new? To investigate why gastric cancer is more prevalent in some countries than others, these authors asked how H. pylori infection affects gene methylation. Here, they compared genomes of normal gastric mucosa from gastric cancer cases and controls, with and without H. pylori infection. They noted changes in methylation correlating with H. pylori infection, including current and prior infections, and identified 438 differently methylated regions associated with H. pylori infections. Interestingly, 152 differently methylated regions correlated with increased gastric cancer risk regardless of H. pylori status. Some of these methylation patterns could lead to biomarkers for detecting disease progression.